2019
DOI: 10.22219/jmb.v9i2.10039
|View full text |Cite
|
Sign up to set email alerts
|

Green Marketing: Strategy for Gaining Sustainable Competitive Advantage in Industry 4.0

Abstract: This study would like to explains conceptual green marketing and its role as a source sustainable competitive advantage in industrial revolution 4.0. The environmental issue is a sizzling topic nowadays as almost every country’s government and society has started to be more aware of these issues. Plus, there is currently a phenomenon of industrial revolution 4.0 which demands business practices to be more consumer-oriented. Public concern over environmental damage has made marketers know the needs and value of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 3 publications
0
12
0
1
Order By: Relevance
“…This means that the raw materials, input items, processes and developments of such products are based on resources that can be preserved and recycled. Purwanti et al (2019) stated that green products are ecological products that put priority on the long term safety of user and the environment, green products are made through not wasting resources and do not involve cruelty to man or animal kind. Additionally, green product quality is measured based on the reflection of environmental features on the product.…”
Section: Green Productmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the raw materials, input items, processes and developments of such products are based on resources that can be preserved and recycled. Purwanti et al (2019) stated that green products are ecological products that put priority on the long term safety of user and the environment, green products are made through not wasting resources and do not involve cruelty to man or animal kind. Additionally, green product quality is measured based on the reflection of environmental features on the product.…”
Section: Green Productmentioning
confidence: 99%
“…In reality the green pricing covers the economic and environmental costs of production and is captured in the final product price which makes pricing in a premium form . According to Purwanti et al (2019) consumers are willing to pay premium price for green products so far there is a perception of additional value in terms of the how the product is environmentally friendly.…”
Section: Green Pricementioning
confidence: 99%
“…Just like Mustika, who stated that the contribution of innovation from green marketing to sustainable development is in the form of reducing the level of waste that can pollute the environment and is contrary to sustainable development goals (D. D. Mustika et al, 2020). Purwanti says, "green marketing able to encourage companies to prepare themselves faster and better; the definition of green marketing has changed over time according to the growing relevance of environmental sustainability" (Purwanti et al, 2019). Kinoti, with the title "Green marketing Intervention Strategies and Sustainable Development: A Conceptual Paper," states that "In this paper, it is suggested that marketing, like any other functional area of business, contributes to the environmental problems facing the world today.…”
Section: Previous Researchmentioning
confidence: 99%
“…The results of research conducted by Mishra et al (2019) state that one of the biggest problems with green area marketing is that there is little effort to academically examine environmental marketing optimally so that company policy, when viewed from the point of view of the use of natural resources as environmentally friendly raw materials environment is still considered less effective. Research by Purwanti et al (2019) shows that implementing green marketing, such as through sales promotion and CSR (corporate social responsibility) programs, can identify well who are paying customers and providers for the company. Through the CSR program, the body shop can analyze predictions on issues or problems that are likely to arise so that the CSR program can be said to be targeting the right target.…”
Section: Access To Successmentioning
confidence: 99%